2016
DOI: 10.1128/jvi.03115-15
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation Sequence and Region in Autographa californica Multiple Nucleopolyhedrovirus ME53 That Are Important for Optimal Baculovirus Production

Abstract: Autographa californica multiple nucleopolyhedrovirus (AcMNPV) is in the family Baculoviridae, genus Alphabaculovirus. AcMNPV me53 is a highly conserved immediate early gene in all lepidopteran baculoviruses that have been sequenced and is transcribed up to late times postinfection. Although me53 is not essential for viral DNA synthesis, infectious budded virus (BV) production is greatly attenuated when it is deleted. ME53 associates with the nucleocapsid on both budded virus and occlusionderived virus, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An illustrative example is the interaction between the Ran-binding protein 5 (RanBP5) of the influenza A virus (IAV) and the PB1-PA dimer in the host [35]. In baculovirus, certain nuclear proteins lacking functional NLS exhibit a sequence serving as a pivotal motif for nuclear translocation.For instance, Liu et al identified amino acid residues 109 to 137 at the N-terminal of ME53, the nuclear protein of AcMNPV, as a potential binding site for other viral or host proteins, including VP39 and GP64 [37].…”
Section: Interaction With Nuclear Entry Proteinsmentioning
confidence: 99%
“…An illustrative example is the interaction between the Ran-binding protein 5 (RanBP5) of the influenza A virus (IAV) and the PB1-PA dimer in the host [35]. In baculovirus, certain nuclear proteins lacking functional NLS exhibit a sequence serving as a pivotal motif for nuclear translocation.For instance, Liu et al identified amino acid residues 109 to 137 at the N-terminal of ME53, the nuclear protein of AcMNPV, as a potential binding site for other viral or host proteins, including VP39 and GP64 [37].…”
Section: Interaction With Nuclear Entry Proteinsmentioning
confidence: 99%
“…Pan et al reported a novel NLS in the baculovirus late expression factor 11, and further research revealed that the NLS of baculovirus LEF-11 is important for viral DNA replication [25,88]. It has been reported that the cNLSs of baculovirus IE-1 and ME53 are critical for optimal levels of budded virus production [27,92]. Moreover, Yu and colleagues identified a bipartite NLS of KRK (residues 83 to 85) and KKVK (residues 120 to 123) that is essential for the final destination of E1 in the nucleus to exert its function during viral replication [93].…”
Section: Requirements For the Localization Of Viral Self-encoded Dmentioning
confidence: 99%